KEPENTINGAN POLITIK JANGKA PANJANG MAHKAMAH KONSTITUSI DAN FENOMENA JUDICIALIZATION OF POLITICS PADA BEBERAPA PUTUSANNYA - Badruzzaman, Zaky (SIYASI: Jurnal Trias Politica, 2023)
This article aims to describe the phenomenon of judicialization of politics in Indonesia. This phenomenon became known at the beginning of the 21st century, which was marked by the resolution of matters relating to public policy, morality, education and political controversies through judicial institutions. The emergence of the judicialization of politics can be seen in the shift in the resolution of political conflicts which were previously resolved through political institutions, namely the MPR, to judicial-based resolution. To be able to see this phenomenon, this article will discuss the brief minutes of the formation of the Constitutional Court in Indonesia. From a socio-historical perspective, the establishment of the Constitutional Court is an institution that is not only intended to fulfill judicial interests, but also expands its presence into the political realm. Apart from that, this article will also explain the decision of the Constitutional Court regarding the institutional position of the Corruption Eradication Committee and the age limit for presidential and vice-presidential candidates to show that the phenomenon of judicialization of politics is clearly present in Indonesia through the Constitutional Court Decision.Tulisan ini bertujuan untuk mendeskripsikan fenomena judicialization of politics di Indonesia. Fenomena ini mulai dikenal pada awal abad ke-21 yang ditandai dengan adanya penyelesaian yang berkaitan dengan perkara kebijakan publik, moralitas, pendidikan dan kontroversi politik melalui lembaga peradilan. Kemunculan judicialization of politics dapat terlihat pada pergeseran penyelesaian konflik politik yang tadinya diselesaikan melalui lembaga politik, yakni MPR menjadi penyelesaian yang berbasis judicial. Untuk dapat melihat fenomena tersebut, artikel ini akan membahas terkait dengan risalah singkat pembentukan Mahkamah Konstitusi di Indonesia. Dalam perspektif sosio-hostoris, pembentukan Mahkamah Konstitusi merupakan lembaga yang bukan hanya dimaksudkan untuk memenuhi kepentingan judicial, namun juga memperluas kehadirannya ke ranah politik. Selain itu, tulisan ini juga akan menguraikan terkait dengan putusan Mahkamah Konstitusi terkait dengan kedudukan kelembagaan KPK dan batas usia capres dan cawapres untuk menunjukan bahwa fenomena judicialization of politics jelas hadir di Indonesia melalui Putusan Mahkamah Konstitusi.